Nogo-A downregulation impairs place avoidance in the Carousel maze but not spatial memory in the Morris water maze - Petrasek, Tomas; Prokopova, Iva; Bahnik, Stepan; Schonig, Kai; Berger, Stefan; Vales, Karel; Tews, Bjorn; Schwab, Martin E; Bartsch, Dusan; Stuchlik, Ales (Neurobiology of learning and memory, 2014)
Nogo-A protein is an important inhibitor of axonal growth, which also regulates neuronal plasticity in the CNS. Mutations in the gene encoding Nogo-A or abnormalities in Nogo-A expression are linked to neuropsychiatric disorders such as schizophrenia. The present study assesses the impact of constitutively reduced expression of Nogo-A on place navigation in a novel transgenic rat model. Two spatial paradigms were used: (1) A battery of tests in the Carousel maze requiring continuous processing of spatial information with increasing demands for the segregation of reference frames and behavioral flexibility and (2) a delayed-matching-to-place version of the Morris water maze (MWM), which requires place navigation and is sensitive to deficits in one-trial-encoded place representation. The Carousel maze testing revealed a subtle but significant impairment in management of reference frames. Matching-to-place learning in the Morris water maze was unaffected, suggesting an intact representation of an unmarked goal. Our results show that Nogo-A deficiency leads to cognitive deficit in processing of the reference frames. Such a deficit may be the result of neuro-developmental alterations resulting from Nogo-A deficiency.
Keywords: Rats, Sprague-Dawley; down regulace; Transgenic rat model; Myelin Proteins; myelinové proteiny; Maze Learning; Rats; prostorové chování; Avoidance Learning; Down-Regulation; Cognitive coordination; genový knockdown; Gene Knockdown Techniques; učení vyhýbat se; Spatial Behavior; Nogo Proteins; Rats, Transgenic; potkani Sprague-Dawley; zvířata; mužské pohlaví; potkani transgenní; Spatial mazes; Animals; krysa rodu Rattus; Spatial navigation; Nogo-A; bludiště - učení; Male; Nogo proteiny